Korelasi Antara Kemandirian Dan Motivasi Belajar Dengan Prestasi Belajar Siswa SMA - Maria Wilda Malo; Lidia Lali Momo (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to know the corelation between indepndent learning with achievement of learning math, the corelation between learning motivation with achievement of learning math, and corelation between independent learning and learning motivation with students’ achievement of learning math class XI in SMA Katolik Waikabubak. This research uses quantitative approach. The population of this research is the students of class XI SMA Katolik Waikabubak totally 132 students. Sampling technique uses by Slovin pattern and 99 students are choosen. The data collecting by questionaire. Hypothesis test uses product moment of corelation test for first hypothesis and the second, meanwhile for the third hypothesis by multiple regresion test. The instrument of validity test uses person’s product moment of corelation and the realibity tes uses Alpha Cronbach. Analysis tes for normality and linearity test apply Kolmogrov-Kmirnov. The result of this investigation, shows that: 1) there is no corelation between independent learning with students’ achievement of learning math, 2) there is corelation between learning motivation with students’ achievement of learning math, 3) there is corelation of independent learning and learning motivation from students with students’ achievement of learning math